Le rêve communautaire de Marie-Claire Blais. Eschatologie et agapé dans le cycle de "Soifs" - Kyloušek, Petr (Wydawnictwo Naukowe UAM, 2013)
Marie-Claire Blais seeks to innovate, throughout her career, her “antimimétique” writing. Her extensive pentalogy - Soifs (1995), Dans la foudre et la lumière (2001), Augustino et le choeur de la destruction (2005), Naissance de Rebecca à l’ère des tourments (2008), Mai au bal des prédateurs (2010) – offers a complex existential questioning of the actual situation of the man. The problem of Evil and Good, which is in the heart of questions and answers, is treated with an original narration, transforming Virginia Woolf’s stream of consciousness. This innovation, however, is rooted in the tradition, namely its baroque poetics and its community orientation, both attached to the affirmation / negation of the catholic heritage that marked Quebec.
Marie-Claire Blais and her community dream. Eschatology and agape in the novel cycle "Soifs"
Keywords: Marie-Claire Blais; Quebec novel; narratology; Baroque poetics; community orientation